Implementing Artificial Intelligence in Teaching Descriptive Text to Grade XI Students: A Qualitative Study at SMA Negeri 1 Dawarblandong Mojokerto - Rifkatuzahro Rifkatuzahro; Dyah Worowirastri Ekowati; Mohammad Syahri (Journal of General Education and Humanities, 2026)
This study aims to describe the implementation of Artificial Intelligence (AI) in teaching descriptive text to eleventh-grade students at SMA Negeri 1 Dawarblandong Mojokerto. The study employed a qualitative descriptive approach involving three English teachers and students who participated during classroom learning activities. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion-drawing techniques. The AI tools used in this study included ChatGPT and several AI-based learning support applications. The findings indicate that AI was implemented in the planning, teaching, and assessment stages. In the planning stage, AI-assisted teachers develop lesson modules, designing learning activities, and selecting appropriate instructional media. During the teaching process, AI-supported interactive learning activities increased student participation through the construction of descriptive text and prompt-based exercises. In the assessment stage, AI helped teachers provide faster feedback and analyze students’ progress more efficiently. Overall, the integration of AI supported teacher efficiency and creativity while also enhancing students’ engagement and learning processes in descriptive text instruction.